Nivolumab plus chemoradiotherapy in locally-advanced cervical cancer: the NICOL phase 1 trial - Rodrigues, Manuel; Vanoni, Giulia; Loap, Pierre; Dubot, Coraline; Timperi, Eleonora; Minsat, Mathieu; Bazire, Louis; Durdux, Catherine; Fourchotte, Virginie; Laas, Enora; Pouget, Nicolas; Castel-Ajgal, Zahra; et al. (Nature communications, 2023)
Concurrent chemoradiotherapy (CRT) with blockade of the PD-1 pathway may enhance immune-mediated tumor control through increased phagocytosis, cell death, and antigen presentation. The NiCOL phase 1 trial (NCT03298893) is designed to determine the safety/tolerance profile and the recommended phase-II dose of nivolumab with and following concurrent CRT in 16 women with locally advanced cervical cancer. Secondary endpoints include objective response rate (ORR), progression free survival (PFS), disease free survival, and immune correlates of response. Three patients experience grade 3 dose-limiting toxicities. The pre-specified endpoints are met, and overall response rate is 93.8% [95%CI: 69.8–99.8%] with a 2-year PFS of 75% [95% CI: 56.5–99.5%]. Compared to patients with progressive disease (PD), progression-free (PF) subjects show a brisker stromal immune infiltrate, higher proximity of tumor-infiltrating CD3 + T cells to PD-L1 + tumor cells and of FOXP3 + T cells to proliferating CD11c + myeloid cells. PF show higher baseline levels of PD-1 and ICOS-L on tumor-infiltrating EMRA CD4 + T cells and tumor-associated macrophages, respectively; PD instead, display enhanced PD-L1 expression on TAMs, higher peripheral frequencies of proliferating Tregs at baseline and higher PD-1 levels at week 6 post-treatment initiation on CD4 and CD8 T cell subsets. Concomitant nivolumab plus definitive CRT is safe and associated with encouraging PFS rates. Further validation in the subset of locally advanced cervical cancer displaying pre-existing, adaptive immune activation is warranted. A combination of chemoradiotherapy followed by brachytherapy is recommended for patients with locally-advanced cervical cancer (LACC), however there is still a high risk of disease recurrence. Here the authors report clinical outcomes and immunologic correlates of a clinical trial of the PD-1 inhibitor nivolumab in combination with chemoradiotherapy in LACC patients.